2017
DOI: 10.1016/j.aap.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Texting while driving, executive function, and impulsivity in college students

Abstract: The purpose of the present study was to investigate the cognitive processes underlying texting while driving. A sample of 120 college students completed a survey to assess how frequently they send and read a text message while driving. Based on this information, students were assigned to one of two groups: 20 students who frequently text while driving and 20 matched-control students who infrequently text while driving but were similar in gender, age, years of education, and years driving. The groups were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 74 publications
4
28
0
Order By: Relevance
“…Given prior studies have laid the theoretical foundations that certain personality traits can predict generalized mobile phone use (Bianchi & Phillips, 2005;Butt & Phillips, 2008) and unsafe driving behaviors (Groeger & Rothengatter, 1998), researchers have started to focus on specific personality attributes that could account for the extra variance in MPUWD. A recent study found participants with a higher level of impulsivity were more likely to text (Hayashi, Rivera, Modico, Foreman, & Wirth, 2017), but the finding from another study discovered this result only applied for men's texting behavior (Struckman-Johnson, Gaster, Struckman-Johnson, Johnson, & May-Shinagle, 2015). Some studies revealed that sensation-seeking is significantly and positively related to interactions to mobile phone tasks while driving (H.-Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given prior studies have laid the theoretical foundations that certain personality traits can predict generalized mobile phone use (Bianchi & Phillips, 2005;Butt & Phillips, 2008) and unsafe driving behaviors (Groeger & Rothengatter, 1998), researchers have started to focus on specific personality attributes that could account for the extra variance in MPUWD. A recent study found participants with a higher level of impulsivity were more likely to text (Hayashi, Rivera, Modico, Foreman, & Wirth, 2017), but the finding from another study discovered this result only applied for men's texting behavior (Struckman-Johnson, Gaster, Struckman-Johnson, Johnson, & May-Shinagle, 2015). Some studies revealed that sensation-seeking is significantly and positively related to interactions to mobile phone tasks while driving (H.-Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, low EF is related to impulsivity, sensation seeking and other risk-taking behaviors in teens [ 11 , 12 , 13 ]. Limited EF due to atypical development may contribute to poor attention and decision making, impulsivity, and the risky driving behaviors that contribute to the elevated crash risk among teen drivers [ 14 , 15 , 16 , 17 ]. However, sensation seeking and rationalized risk-taking (i.e., weighing risks and benefits rather than impulsive risk-taking) also appear to increase with EF ability in adolescence (see the Life-span Wisdom Model [ 13 ]), indicating a complex relationship between EF and adolescent risk-taking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A similar argument was made regarding executive function—cognitive abilities for adaptive functioning that allow for goal‐oriented, flexible, and autonomous behavior (Spinella, ). As with excessive discounting, impaired executive function has been shown to be associated with addictive disorders, such as substance abuse (Goldstein & Volkow, ), pathological gambling (Reid, McKittrick, Davtian, & Fong, ), and most notably, texting while driving (Hayashi, Foreman, Friedel, & Wirth, ; Hayashi, Rivera, Modico, Foreman, & Wirth, ). In this manner, both excessive discounting and impaired executive function occur across various impulsivity‐related problems, suggesting that they may be transdisease processes.…”
Section: Discussionmentioning
confidence: 99%